1983
DOI: 10.1073/pnas.80.6.1631
|View full text |Cite
|
Sign up to set email alerts
|

Senescent cell antigen is immunologically related to band 3.

Abstract: IgG autoantibodies in human serum selectively bind to a glycopeptide antigen that appears on senescent and damaged cells in situ. We identified the membrane protein from which the senescent cell antigen is derived by using a phagocytosis-inhibition assay and immunoautoradiographic gel staining and electroblotting techniques. Results of the phagocytosis-inhibition assay revealed that only the purified transmembrane glycoprotein designated "band 3" and senescent cell antigen inhibited the phagocytosis of erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
97
0
2

Year Published

1983
1983
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 37 publications
5
97
0
2
Order By: Relevance
“…However, they do not agree on the molecular changes responsible for generating the antigen. Our evidence suggests that senescent-cell antigen is derived from band 3, probably by degradation (10,(25)(26)(27)(28)(29)(30)(31); Lutz and his colleagues have suggested that senescent-cell antigen is a dimer ofband 3 (32); Sayare et al (33) have shown that band 3 can cross-link with hemoglobin under oxidative conditions; and Low et al (34) have presented evidence that clustered band 3 can generate senescent-cell antigen. These membrane events are not mutually exclusive.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…However, they do not agree on the molecular changes responsible for generating the antigen. Our evidence suggests that senescent-cell antigen is derived from band 3, probably by degradation (10,(25)(26)(27)(28)(29)(30)(31); Lutz and his colleagues have suggested that senescent-cell antigen is a dimer ofband 3 (32); Sayare et al (33) have shown that band 3 can cross-link with hemoglobin under oxidative conditions; and Low et al (34) have presented evidence that clustered band 3 can generate senescent-cell antigen. These membrane events are not mutually exclusive.…”
mentioning
confidence: 76%
“…Senescent-cell antigen is a glycosylated 4.5 region polypeptide that appears to be derived from band 3 (5,8,10,(25)(26)(27). Senescent-cell antigen is located on an extracellular portion of band 3 that includes most ofthe 38-kDa carboxyl-terminal segment and 30% ofthe anion-transport region (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong evidence that naturally occurring antibodies recognizing senescent RBCs in vivo recognize Band 3. 38 Thus, we used the antimouse Band 3 mAb 34-3C for opsonization, a mAb that induces RBC phagocytosis both in vivo and in vitro and shows enhanced binding to aged murine RBCs in vivo. 23,28,31 In the presence of serum, phagocytosis of IgG-opsonized WT Ox-RBCs was increased, compared with equally opsonized untreated WT RBCs (84.3 Ϯ 8.0 vs 52.3 Ϯ 0.5 RBCs/100 macrophages, respectively; P Ͻ .05) ( Figure 4A).…”
Section: Cd47 On Ox-rbcs Can Still Inhibit Fc␥r-mediated Phagocytosismentioning
confidence: 99%
“…The antigen in fact is recognized by the Fab region of autologous specific IgG [5,6] which attaches to it and initiates the removal of cells by macrophages. Senescent cell antigen is immunologically related to band 3 [3,7] and is located in an extracellular portion of it [3]. The molecular changes underlying the formation of senescent cell antigen and marking erythrocytes as aged are under investigation.…”
Section: Introductionmentioning
confidence: 99%